2014
DOI: 10.1016/j.pbb.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Y2 receptor-mediated mossy fiber plasticity is implicated in nicotine abstinence-related social anxiety-like behavior in an outbred rat model of the novelty-seeking phenotype

Abstract: Experimentally naïve outbred rats display varying rates of locomotor reactivity in response to the mild stress of a novel environment. Namely, some display high rates (HR) whereas some display low rates (LR) of locomotor reactivity. Previous reports from our laboratory show that HRs, but not LRs, develop locomotor sensitization to a low dose nicotine challenge and exhibit increased social anxiety-like behavior following chronic intermittent nicotine training. Moreover, the hippocampus, specifically hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…In addition, the brain-penetrant Y2 receptor antagonist JNJ31020028 has also anxiolytic properties. JNJ31020028 reverses the anxiogenic effect of alcohol withdrawal and nicotine-induced social anxiety-like behaviour (6264). Surprisingly, conventional Y2 receptor knockout has yielded mixed results.…”
Section: Role Of Npy In Anxietymentioning
confidence: 99%
“…In addition, the brain-penetrant Y2 receptor antagonist JNJ31020028 has also anxiolytic properties. JNJ31020028 reverses the anxiogenic effect of alcohol withdrawal and nicotine-induced social anxiety-like behaviour (6264). Surprisingly, conventional Y2 receptor knockout has yielded mixed results.…”
Section: Role Of Npy In Anxietymentioning
confidence: 99%
“…Consistently, other authors showed that rats classified as low responders according to their locomotor response to novelty following an injection of nicotine, showed nicotine-induced CPP after a long- but not short-term conditioning procedure, while rats classified as high responders did not show CPP under any condition ( 212 ). Also, rats selected as high locomotor responders to novelty showed enhanced social anxiety-like behavior during abstinence after repeated nicotine exposure ( 213 216 ).…”
Section: Predisposing Endophenotypes For Nicotine Taking and Seeking mentioning
confidence: 99%
“…Such an enhanced locomotor response to novelty is useful for studying sensation seeking in humans [ 41 ]. Kahler et al [ 42 ] revealed that increased sensation seeking was a predictor of a reduced smoking cessation rate in humans, while in rats, an increased motor response to novelty contributed to the enhanced social anxiety-like phenotype during nicotine withdrawal [ 43 ]. It can therefore be assumed that the inhibitory effect of subchronic lorcaserin on motility in drug-weaned rats reflected a positive rather than negative (i.e., sedative effect) effect on withdrawal signs in animals.…”
Section: Discussionmentioning
confidence: 99%